2020
DOI: 10.3390/ijerph17217848
|View full text |Cite
|
Sign up to set email alerts
|

Using Machines or Free Weights for Resistance Training in Novice Males? A Randomized Parallel Trial

Abstract: This study compared the effect of a resistance training (RT) program with machines, free weights, or a combination of both on changes in anthropometrics, strength, and functional ability in novice adult males. Thirty-six male novices in RT (18–45 years) followed a 10-week RT program. Participants were randomly assigned to one of three groups (N = 12 each): machines only; free weights only; or switching from machines to free weights (after 5 weeks). Muscle size (circumferences of upper arm, thigh and chest), st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(54 citation statements)
references
References 29 publications
0
43
0
11
Order By: Relevance
“…A summary of the methodology and main findings of included studies are displayed in Table 2. Seven studies assessed the effects of exercise variation on measures of both muscle hypertrophy and strength (2,10,14,20,39,40), and 1 assessed only muscular strength (15). The studies from Aerenhouts and D'Hondt (2), Chaves et al (10), Costa et al (14), Costa et al (15), Fonseca et al (20), and Rossi et al (40) compared 1 fixed predetermined exercise per muscle group vs. predetermined variations of exercises (e.g., A vs. A, B, C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A summary of the methodology and main findings of included studies are displayed in Table 2. Seven studies assessed the effects of exercise variation on measures of both muscle hypertrophy and strength (2,10,14,20,39,40), and 1 assessed only muscular strength (15). The studies from Aerenhouts and D'Hondt (2), Chaves et al (10), Costa et al (14), Costa et al (15), Fonseca et al (20), and Rossi et al (40) compared 1 fixed predetermined exercise per muscle group vs. predetermined variations of exercises (e.g., A vs. A, B, C).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 7 studies that investigated muscular strength, Aerenhouts and D'Hondt (2) estimated 1RM strength, Baz-Valle et al (5), and Rauch et al (39) employed 1RM testing, whereas Chaves et al (10) conducted isometric strength tests, and Costa et al (15) conducted both 1RM and isometric strength tests. Aerenhouts and D'Hondt (2), Baz-Valle et al (5), Rauch et al (39), and Chaves et al (10) showed similar strength responses between varied and nonvaried protocols. Conversely, Fonseca et al (20) observed greater gains favoring varied-exercise groups, whereas Costa et al (15) and Rossi et al (40) observed conflicting results depending on the specific test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwanbeck et al (160) reported similar increases in biceps brachii and quadriceps femoris muscle thickness regardless of whether participants used machines or freeweights over an 8-week study period; the effects of combining modalities was not investigated. Aerenhouts et al (161) showed no benefit to switching between machines and free-weights midway during a 10-week RT program compared to either modality alone; however, hypertrophy was estimated by circumference measurements, hence providing only a crude estimate of changes in muscle mass.…”
Section: Gaps In the Literaturementioning
confidence: 99%
“…Вступ. Проблемою удосконалення тренувального процесу в бодібілдингу за рахунок розробки інноваційних програм занять з використанням різноманітних комплексів вправ, методів, принципів, механізмів корекції навантажень та варіативності співвідношення величини параметрів їх компонентів направлених на підвищення адаптаційних резервів організму на тлі прискореного зростання м'язової маси тіла та силових можливостей організму спортсменів протягом останніх десятиліть займалась значна кількість провідних фахівців в даному напрямку науково-дослідної роботи [1][2][3][4].…”
Section: особливості впливу навантажень з використанням вправ на трен...unclassified